PERBANDINGAN METODE RESITASI DAN METODE DISKUSI TERHADAP HASIL BELAJAR SISWA - Denni, Dina; Prasetyo, Moh. Mulyadi; Akhmad, Nur Amaliah (Indonesian Journal of Educational Technology, 2024)
This study aims to compare the effectiveness of the recitation method and the discussion method on the learning outcomes of seventh-grade students at SMP Negeri 1 Pana. The background of this research is the need to address student boredom and increase engagement in the learning process, which is predominantly lecture-based. This study uses a non-equivalent control group design with a quantitative approach. Seventh-grade students were divided into two groups: the experimental group using the discussion method and the control group using the recitation method. Data collection was conducted through pretests and posttests, analyzed using descriptive and inferential statistics. The results show that both methods successfully improved student learning outcomes. However, the discussion method proved to be more effective, with a more significant increase in posttest scores compared to the recitation method. Inferential statistical analysis using the t-test showed a significant effect of the discussion method on student learning outcomes (p < 0.05). The conclusion of this study is that the discussion method is more effective in improving student learning outcomes, as well as developing social skills and critical thinking abilities through active and collaborative interaction. These findings provide practical recommendations for educators to implement the discussion method in the learning process to enhance education quality.